2017
DOI: 10.1016/j.neuron.2017.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Excitatory Synapses in the Absence of Glutamatergic Neurotransmission

Abstract: SUMMARY Synaptic excitation mediates a broad spectrum of structural changes in neural circuits across the brain. Here, we examine the morphologies, wiring, and architectures of single synapses of projection neurons in the murine hippocampus that developed in virtually complete absence of vesicular glutamate release. While these neurons had smaller dendritic trees and/or formed fewer contacts in specific hippocampal subfields, their stereotyped connectivity was largely preserved. Furthermore, loss of release di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
114
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(136 citation statements)
references
References 86 publications
(138 reference statements)
16
114
6
Order By: Relevance
“…Although informative, these experiments were indirect. The neuroligin-induced increase in synapse density was activity-dependent (Chubykin et al, 2007), suggesting that it differs from physiological initial synapse formation, which is activity-independent (Verhage et al, 2000; Sando et al, 2017; Sigler et al, 2017). Moreover, the original conclusion that neuroligin overexpression increases spine density was based on comparing expression of labeled neuroligins with a diffusible marker; more careful recent quantifications suggested that overexpressed neuroligins do not increase spine numbers, but only synapse numbers (Chanda et al, 2017).…”
Section: Neuroliginsmentioning
confidence: 99%
“…Although informative, these experiments were indirect. The neuroligin-induced increase in synapse density was activity-dependent (Chubykin et al, 2007), suggesting that it differs from physiological initial synapse formation, which is activity-independent (Verhage et al, 2000; Sando et al, 2017; Sigler et al, 2017). Moreover, the original conclusion that neuroligin overexpression increases spine density was based on comparing expression of labeled neuroligins with a diffusible marker; more careful recent quantifications suggested that overexpressed neuroligins do not increase spine numbers, but only synapse numbers (Chanda et al, 2017).…”
Section: Neuroliginsmentioning
confidence: 99%
“…Also, the extent to which neurotransmitter release in general drives synaptic and neuronal development remains a controversial question. Indeed, a recent study examining hippocampal CA1 subfield pyramidal neurons from mice that lacked both spontaneous and evoked release (due to the absence of key SNARE proteins) found no profound changes (Sigler et al, ) while another study which used tetanus toxin to block release describe the loss of almost half of excitatory synapses on to the same neuronal type, with impaired dendritic arborizations (Sando et al, ). There is a great deal of evidence from the literature that using different approaches to modulating activity can result in different effects on synapse formation (Andreae & Burrone, ), and indeed, it is unclear how much of an impact tetanus toxin has on early spontaneous release (Andreae & Burrone, ; Choi et al, ; Shin et al, ; Verderio et al, ).…”
Section: Conclusion and Controversiesmentioning
confidence: 99%
“…Such initial transmission could guide pre-with postsynaptic assembly by activating fluctuating, mobile postsynaptic NT receptors which might allow postsynaptic Ca 2+ influx to activate signaling cascades, lead to NT-receptor anchorage and facilitate synapse assembly [138]. In line with this, synaptic activity was shown to be critical to ensure proper synapse morphology and development [139], while basal synaptogenesis mechanisms appear to be activity independent [20,140,141]. As Unc13B hardly contributes to AP-evoked release at mature synapses, a key functional role may relate to Unc13B mediated, AP-independent, spontaneous synaptic activity, which is thought to fulfill essential signaling roles [142].…”
Section: Perspective and Conclusionmentioning
confidence: 99%